Normalisasi Selokan Buangan Air Sawah, Air Hujan, dan Drainase Perumahan - Syamsul Hadi; Anggit Murdani; Santoso Santoso; Agus Sujatmiko; Sugeng Hadi Susilo (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
Wild flow of water below the surface of the land toward the road and the foundation of houses, road damage due to land subsidence, damage to the houses foundations, mosquito larvae lodged due to standing water, and the emergence of foul odors as a problem faced. The purpose of service is to help the community to expedite the flow of water from the rice-fields, rain and household waste, drain the gutter as a source of disease (dengue fever) through the gutter, restore the flow of wild water into the gutter, and maintain a healthy hygiene environment. The method applied was consultation with residents to determine the construction design of the channel, dismantling the broken gutters and there was a wild flow of water to the street/house yard, casting with a high-strength concrete until strength enough, repairing the cracked gutter walls with cement paste, and submitting the results of normalization to the Chairman of the local Neighborhoods Association/RT. Normalization results in the form of clean gutters, rice-fields-rain-discharged water from houses flowing through the gutters smoothly without leaking and no puddles, there is a synergy between State Polytechnic of Malang and the community in obtaining a smooth flow of water from rice-fields/rain/discharged houses into the house sewer in RW 06 Tasikmadu-Lowokwaru-Malang which implies awareness of citizens of a clean, healthy and orderly environment. Conclusions of the results of normalization as a flow of water from various origins through a structured sewer smooth water flow, prevention of disease, and providing beauty environmental.